ABORSI DALAM TINJAUAN HUKUM ISLAM - Nilda Susilawati (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2015)
Abortion in Islamic Perspective. Abortion is an act of ending the pregnancy or an act ofconception before the embrio survive outside the mother’s womb. The islamic scholars are of differentopinion regarding the verdict of abortion for the fetus before the soul is blowed. The reason why someof Islamic scholars are allowing the abortion is that there is no killing on it, because it has no soul yet.But the other of islamic scholars are prohibited the abortion because it is similiar to killing the baby,except in the urgent condition. Most of Islamic scholars agreed that if the baby soul has been revealed,then it is prohibited to do an abortion, because the baby is a live, and it is similar to an act of killing aliving human. And the sentence is to pay kafarat and diat and ghirrah that is to free the faithfulservant. And if he is unable to do that he must fast for two months continously, as mentioned in suratan-nisa’ verse 92